2009
DOI: 10.1007/s11482-009-9075-9
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Conceptual Model of Quality of Life for Older Adults Based on a Synthesis of the Literature

Abstract: Quality of life is fast becoming a standard of measure of long-term care and gerontological service outcomes. Although the issue of quality of life has been of increasing interest in the field of aging, there has been little agreement as to the clarity and definition of the concept and how to measure it, especially as it relates to older adults. Presented here is a comprehensive, integrated model of quality of life that was developed by synthesizing existing constructs within the literature into six major life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…Whilst these studies are important contributions to understanding and practice (see for example: Bowling et al ., ; Degenholtz et al ., ; Harmer & Orrell, ; Kelley‐Gillespie, ), gerontological nursing literature that addresses care home residents’ perceptions and perspectives of quality of life predominantly follows a Western discourse and paradigm. For example, when the keywords ‘Lebanon’ and ‘Quality of Life’ are applied in combination with the MeSH terms ‘nursing home(s)’, ‘care home(s)’, ‘residential home(s)’, ‘well‐being’, ‘nursing’, ‘care’ to all relevant search engines, including PsychoINFO (1980–2012), PubMed/MEDLINE (1980–2012), CINAHL Plus (1980–2012) and Cochrane (1993–2012), only one study was found.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Whilst these studies are important contributions to understanding and practice (see for example: Bowling et al ., ; Degenholtz et al ., ; Harmer & Orrell, ; Kelley‐Gillespie, ), gerontological nursing literature that addresses care home residents’ perceptions and perspectives of quality of life predominantly follows a Western discourse and paradigm. For example, when the keywords ‘Lebanon’ and ‘Quality of Life’ are applied in combination with the MeSH terms ‘nursing home(s)’, ‘care home(s)’, ‘residential home(s)’, ‘well‐being’, ‘nursing’, ‘care’ to all relevant search engines, including PsychoINFO (1980–2012), PubMed/MEDLINE (1980–2012), CINAHL Plus (1980–2012) and Cochrane (1993–2012), only one study was found.…”
Section: Quality Of Lifementioning
confidence: 99%
“…This model is used consistently within the literature (Estes & Swan, 1992;Kelley-Gillespie, 2009;Rowan et al, 2011;Rudd, 1996;Van Beveren & Hetherington, 1995) and measures four major components of HCB service delivery: equity, accessibility, quality, and efficiency. Equity refers to the extent that adequate and responsive health services are available for those in need of care, irrespective of the ability to pay.…”
Section: Methodsologymentioning
confidence: 99%
“…As Gonzalez et al note, complex systems have multiple components that interact in dynamical ways and change over time. Kelley-Gillespie (2009) recently synthesized the literature on QoL and presented an integrated conceptual model of QoL for older adults. She noted the lack of consensus on models and measures, despite the widespread recognition of the role of QoL for older adults, and highlighted the importance of going beyond physical health-related domains and the medical model approach.…”
Section: Quality Of Life Conceptual Modelmentioning
confidence: 99%